Evaluación de la Incidencia de Plagas en Sistemas de Cultivo de Maíz y su Impacto Ambiental - Vela Tang, Denis Hernán (2004)
The present research was realized in the sectors of San Mateo (district of Moyobamba) an Limabado, (district of Yantalö), both in the province of Moyobamba in San Martin departmen It as aims: Evaluate the incidence of pest in the grown of corn systems and its environment impact, in addition to promote the habets of agronomics grown in asociated systems as a alternative to decrease the proliferation on pests, the use of agro-chemists through the existenc of natural controllers beneficent in those agro zones, for the grown of corn; determinate th density of pests and natural controlers; inspect the damage caused by the pest in the grown c corn system in experimental plot of lands and to identify an test the environmental impacts i those agronomic sown field systems. The factors in study were distributed in two experimental sectors which were constituted i three treatments (incluiding the witness); being associated in different systems of sowing an grown of corn: Policultivation I (PI), policultivation 2 (P2), monocultivation (M). For which used seve variates of agro products sowing traditionally in the province of Moyobamba the experiment design used in this work was the design of blocks completely at random, with two repetitions i each experimental sector. It was realized six tests of incidencing of pests for Diabrötica Spodoptera spp, Helicoperva zea, Diatraea saccharalis. In addition it obtained the pest density and invertebrates evaluation, in the period from October 2002 to January 2003. At the end of the experiment reached to the following conclutions: In the incidence of pests evaluation (Diabrötica spp, Spodoptera spp, Diatrae saccharalis and Helicoperva zea), in conclution during the investigation the treatmer which reported the mayor grade of incidencing in the attack was the monocultivatio treatment (M); so on the policultivation I (PI ) and the policultivation 2 (P2) treatment were which obtained a smaller grade of incidencing in the pests attack 2. The spacial diversification, the estability and the production of the agro-ecosystem presented in the policultivation which was stuied letted to obtain a high productivit. and an elevate proportion of the gross and net product of the harvest, all this withou use big emergy supply; which in the practice becomes a better approaching of th agro-ecosystem and economic saving to the producer. 3. The policultivation 01 and 02 turned out more producting than the monocultivati01 reporting a high statis-tic meaning, this can be explained as a largest biology efficienc: of the policultivation or as smallest requiepment of area of this system, to produce th largest o the same quantity of product than the monocultivation. The physica production total was always superior in the policultivation for the two fields studied consequently the gross income result superior in the policultivation for a wide rank o price relation (corn/ yucca, sachapotato, huasca and panamito bean) such a (corn/banana, peanut, bean of stick) according to the pure corm. 4. In relation to he impact environmental evaluation, in can mention that thi environmental factors presented a high impact valoration which represents that thu swoing system used dedn't generate negative environmental impacts as high as affect the environmental.